Serological profile of Toxoplasma gondii and Neospora caninum infection in commercial sheep from São Paulo State, Brazil - Langoni, Hélio [UNESP]; Greca Junior, Haroldo [UNESP]; Guimaraes, Felipe F. [UNESP]; Ullmann, Leila S. [UNESP]; Gaio, Fernanda Conceição [UNESP]; Uehara, Robson S. [UNESP]; Rosa, Eric P. [UNESP]; Amorim, Rogerio Martins [UNESP]; Da Silva, Rodrigo C. [UNESP] (Elsevier B.V., 2011)
Neosporosis and toxoplasmosis are two important infections in young and adult sheep, leading to low production and abortion. This study aimed to determine the frequency of antibodies to Toxoplasma gondii and Neospora caninum in sheep from the eastern region of São Paulo State, Brazil. Serum samples (382) were collected from the sheep and assayed for T. gondii through modified agglutination test (MAT) and indirect fluorescent antibody test (IFAT), and for N. caninum antibodies, through IFAT, with cut-off titers equal to 16 (T. gondii) and 25 (N. caninum). All frozen samples were sent to the Center for Zoonoses Research (NUPEZO), Department of Veterinary Hygiene and Public Health (DHSVP), FMVZ, UNESP, for serological tests. A total of 71/382(18.6%) samples reacted to T. gondii, especially at titers 16 (28; 39.4%), 64(15; 21.1%), 256 (21; 29.6%) and 1024 (6; 8.5%) by MAT, and 16(34: 47.9%), 64 (18; 25.4%), 256 (14; 19.7%) and 1024 (5; 7%) by IFAT. As regards N. caninum, 49/382 (12.8%) samples reacted at titers 25 (17; 34.7%), 50 (11; 22.5%), 100 (11; 22.5%), and >= 200 (10; 20.4%). These animals presented infection but no clinical signs. Six and ten animals had high titers for toxoplasmosis and neosporosis. No significant association was observed between antibodies for both parasites (P = 0.535) according to Fisher's exact test, and no correlation was found between T. gondii (MAT) and N. caninum antibody titers (r = -0.0068; P=0.895), T. gondii (IFAT) and N. caninum antibody titers (r = -0.0025; P = 0.961). Thus, T. gondii and N. caninum infections were observed in farms located in São Paulo State, where sheep play an important economical role for the national and regional business. (C) 2010 Elsevier By. All rights reserved.
Keywords: Toxoplasma gondii; Neospora caninum; Sheep; Infection; Serology; Public health